Clinical profile and outcome of diabetic foot ulcers - Boopathy, D.; Asokan, P. K.; Yeshwanth, T. R. (International Journal of Research in Medical Sciences, 2023)
Background: Diabetes mellitus is a common metabolic endocrine disorder, once prevalent in developed countries has become the leading ‘global epidemic’. WHO estimated that in the year 2000. Roughly 3% of the total world population had Diabetes. In India around 61million of general population affected in 2011 which may rise to 101 million by 2030. The aim of the study was to study the clinical profile and outcome of diabetic foot ulcers. The clinical profile of 120 patients with diabetic foot ulcer was studied. Methods: Patients with diabetic foot ulcer of both genders with age above 30 years willing to participate were included in the study. All patients were subjected to routine diabetic work up with Doppler study and X-ray foot to rule out bone involvement. Results: The majority of patients with diabetic foot ulcers were of age group 51 to 60 years, male predominant, 84 patients out of 120 isolated included for study, 24 (28.6%) isolates had Klebsiella, 46(54.8%) isolates Pseudomonas, 14 (16.7%) isolates has E.coli. Conclusions: Our study gives important information that diabetic foot ulcer is more common among middle-aged people with male predominance which gives the importance of screening diabetic patients for neuropathy and peripheral vascular disease.